IMPLEMENTASI SISTEM PEMESANAN MAKANAN BERBASIS QR CODE UNTUK USAHA MIKRO, KECIL DAN MENENGAH - Ria Manurung; Tetty Tiurma Uli Sipahutar (LPPM Poltek ST Paul, 2024)
This research aims to improve efficiency in providing menu services to customers and efficient use of paper to satisfy cafe customers while saving paper or paperback costs. QR code technology was chosen because it provides a fast, easy, convenient, accurate, and automatic data collection method. Integrating QR code technology into the menu presentation management system allows the cafe to provide food and drinks ordered by customers precisely, effectively, and efficiently. System development using the waterfall method, commonly called linear sequential, starts from analysis, design, coding, testing, and maintenance stages. Based on hypothesis testing, the Sig value is smaller than 0.05, so H0 is rejected, and H1 is accepted. Implementing a QR Code-Based Food Ordering System for Micro, Small, and Medium Enterprises, with a Radio Kopi Cafe case study, increases efficiency. This system shows that the average time before using the system is 7.42 minutes and the average time after using the system is 4 minutes, so the results of the study concluded that the development of this system can be used to speed up the ordering process on the Implementation of QR Code-Based Food Ordering System for Micro, Small and Medium Enterprises with a case study of Radio Kopi Cafe.